Growth and development of oriental fruit fly, Bactrocera dorsalis hendel (Diptera: Tephritidae) reared on sweet potatoes (Ipomoea batatas L.) based artificial diet - Salmah M.; Nurul Fatihah M. Y.; Hailmi M. S.; Norhayati N. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
A study to determine the growth and development of B. dorsalis reared on sweet potatoes-based artificial diet (Ipomoea batatas L.) was conducted under laboratory conditions. Four types of diets used were; orange sweet potato (OSP), purple sweet potato (PSP), white sweet potato (WSP) and wheat germ (WG) as a standard diet. Biological parameters recorded were; number of pupae, pupae weight (mg), pupae and adult survival (%), number of adult emergences, developmental time from eggs to adults’ stage (day), and adult longevity (day). Results showed that among the diet tested, the WG based diet displayed a significant difference (P<0.05) on the growth and development of B. dorsalis particularly on number of pupae, pupa and adult survival and developmental time from egg to adult. However, no significant difference (P>0.05) was shown on pupa weight between WG, OSP, and WSP diet. Adult longevity of B. dorsalis also showed no significant difference (P>0.05) among all the diets. Based on the results obtained, the growth and development of B. dorsalis reared on sweet potatoes based diet was as good as the standard wheat germ-based diet and showed a potential as a main new source of diets for B. dorsalis mass rearing especially in biological control program of the fruit flies.